The polymorphism of chicken-type lysozyme gene in Japanese flounder (Paralichthys olivaceus) and its association with resistance/susceptibility to Listonella anguillarum. Issue 66 (July 2017) - Liu, Jinxiang; Zhou, Nayu; Fu, Ruixue; Cao, Dandan; Si, Yu; Li, Aoyun; Zhao, Haitao; Zhang, Quanqi; Yu, Haiyang
Abstract: Lysozyme is a crucially spread hydrolase in organisms that can defend against bacterial infection in innate immunity. In this study, we successfully sequenced the coding region of chicken-type lysozyme gene ( PoLysC ) in Paralichthys olivaceus and identified nine single nucleotide polymorphisms (SNPs). We then amplified the 2500 bp promoter region of lysozyme and identified the eight sites of polymorphisms. All SNPs were genotyped between susceptible and resistance groups after Listonella anguillarum challenge. One of these SNP sites in the codon of PoLysC was genotyped and determined to be a significant marker by analyzing its distribution in the susceptible and resistant groups. As a nonsynonymous mutation, the frequency of 140G/C genotype in the resistant group was higher (67.74%) than that in the susceptible group (32.26%). The linkage between SNP140 and polymorphisms in the promoter region was also studied. Results revealed that the frequency of haplotype CC-536 /CC-1200 /GG140 in the resistance group was significantly higher than that in the susceptible group. The quantitative expression of lysozyme gene in the resistant group was also higher than that in the susceptible group. This finding indicated that the linkage between polymorphism −536 and −1200 sites in promoter and SNP140 in codon sequence was associated with the resistance of P. olivaceus to L. anguillarum. All these results suggest that the mutations in promoter and coding region were related to changes in PoLysC for resisting L. anguillarum . The haplotype CC-536 /CC-1200 /GG140 was a potential marker and can thus be applied to selective breeding for the disease resistance of P. olivaceus . Highlights: The SNPs of PoLysC in CDS and promoter were identified in Paralichthys olivaceus. The frequency of haplotype CC-536/CC-1200/GG140 in resistance group was higher than in susceptibility group. The mutation of PoLysC in promoter and coding region had the relationship in resist with Listonella anguillarum. The expression of PolysC was higher in resistant group than in susceptible group.